Assessment of Microstructural, Mechanical and Electrochemical Properties of Ti–42Nb Alloy Manufactured by Electron Beam Melting - Kozadaeva, Maria; Surmeneva, Maria; Khrapov, Dmitriy; Rybakov, Vladimir; Surmenev, Roman; Koptyug, Andrey; Vladescu (Dragomir), Alina; Cotrut, Cosmin Mihai; Tyurin, Alexander; Grubova, Irina (Materials, 2023)
The β-type Ti–42Nb alloy has been successfully manufactured from pre-alloyed powder using the E-PBF method for the first time. This study presents thorough microstructural investigations employing diverse methodologies such as EDS, XRD, TEM, and EBSD, while mechanical properties are assessed using UPT, nanoindentation, and compression tests. Microstructural analysis reveals that Ti–42Nb alloy primarily consisted of the β phase with the presence of a small amount of nano-sized α″-martensite formed upon fast cooling. The bimodal-grained microstructure of Ti–42Nb alloy comprising epitaxially grown fine equiaxed and elongated equiaxed β-grains with an average grain size of 40 ± 28 µm exhibited a weak texture. The study shows that the obtained microstructure leads to improved mechanical properties. Young’s modulus of 78.69 GPa is significantly lower than that of cp-Ti and Ti–6Al–4V alloys. The yield strength (379 MPa) and hardness (3.2 ± 0.5 GPa) also meet the criteria and closely approximate the values typical of cortical bone. UPT offers a reliable opportunity to study the nature of the ductility of the Ti–42Nb alloy by calculating its elastic constants. XPS surface analysis and electrochemical experiments demonstrate that the better corrosion resistance of the alloy in SBF is maintained by the dominant presence of TiO2 and Nb2O5. The results provide valuable insights into the development of novel low-modulus Ti–Nb alloys, which are interesting materials for additive-manufactured implants with the desired properties required for their biomedical applications.